Thermoluminescence Dating of Late Pleistocene Sediments, St. Lawrence Lowland, Québec - Lamothe, Michel; Huntley, David (Géographie physique et Quaternaire, 1988)
ABSTRACTThis paper presents the results of a thermoluminescence (TL) dating program applied to waterlaid sediments of Late Pleistocene age, collected in the central St. Lawrence Lowland, in eastern Canada. The apparent TL ages were obtained using a partial bleach method (R-Gamma) in which the TL from light-sensitive traps is separated from the total TL. Fluvial (modern), marine (late-glacial) lacustrine (interstadial) and glacio-lacustrine (stadial) sediments yielded apparent ages ranging from 4 to 135 ka, and in general, these ages agreed with available stratigraphic evidence. Whilst testing the zeroing assumption, apparent TL ages obtained from modern fluvial and late glacial sediments suggest that laboratory overbleaching or insufficient natural bleaching may result in over-estimation of the apparent TL ages by 4-5 ka. All samples display anomalous fading, a problem that can be overcome by introducing a three month delay between artificial irradiation and glowing. Future research should focus on sediments for which the age as well as the sedimentology are well documented, such as the late glacial Champlain Sea sediments.